Effectiveness of a marital counseling program to improve the skill of Conflict management among mothers of children with autism spectrum disorder - Mhaidat, Fatin (Edelweiss Applied Science and Technology, 2024)
This study aimed to discover the effectiveness of a marital counseling program based on the model (Gottman’s model) to improve conflict management skills in a sample of mothers with autism spectrum disorder. The study sample consisted of (24) women who have a child with autism spectrum disorder. These women obtained the lowest scores on the study scale of conflict management skills, after applying the scale to a sample of (70) women who have a child with autism spectrum disorder and who visit the (Noor Al Hussein) Foundation in Amman and the Al-Ataa Comprehensive Center and Al-Razi for Special Education. These centers provide special services for children with autism spectrum disorder, in addition to family services for their families. Participants who agreed to adhere to the counseling program were randomly distributed into two equal groups. An experimental group and a control group, each group included (12) participants who underwent a pre-measurement and a post-measurement. To achieve the study objectives, the Gottman program was developed, consisting of 12 sessions, each session lasting (90) minutes, at a rate of two sessions per week. The results showed statistically significant differences at the level (0.05≥α) on the conflict management scale and on all dimensions of the scale, and the differences were in favor of the experimental group.